PENGARUH SISTEM PENGENDALIAN INTERN TERHADAP FRAUD: (Studi pada PT. Sinar Kurnia Cemerlang Gorontalo) - RAHMA RIZAL (PROGRAM STUDI AKUNTANSI - UNIVERSITAS MUHAMMADIYAH KUPANG, 2015)
The aim of the research is to find out the influence and the amount of contribution of independentvariables consisting of organizational structure (X1), the quality of employees (X2), and protectionof assets (X3) simultaneously positive effect on fraud (Y). Data obtained from the primary data inthe form of a questionnaire that dibagaikan to all employees, including the leadership of the PTSinar Kurnia brilliant totaling 30 people. Data were analyzed using path analysis or path analysis.The results showed that the internal control system consists of the organizational structure (X1),the quality of employees (X2), and protection of assets (X3) simultaneously berngaruhsignificantly against fraud amounted to 62.6%. While partially the effect of organizationalstructure variables (X1) of 50.9%, the variable quality of employees (X2) amounted to 25.8%, andvariable protection against assets (X3) of 15.7% against fraud. and the remaining 37.4% isexplained reasons - other reason not examined.